Interactive Learning Media for Better Learning Outcomes in Elementary School: A Systematic Literature Review - Aryfien, Wahyu Noor; Atmojo, Idam Ragil Widianto; Matsuri, Matsuri (Mimbar Sekolah Dasar, 2025)
The rapid development of digital technology is impacting the learning system in elementary schools and increasing students' screen time. Currently, teachers in Indonesia lack adequate digital competencies, which has become one of the factors affecting students' learning outcomes. This research aims to provide scientific evidence that learning through the use of interactive learning media can improve students' learning outcomes. This study employs the PRISMA method for a systematic literature review, utilizing internationally reputable databases such as Scopus, ScienceDirect, Springer, and ProQuest, covering publications from 2020 to 2024. A total of 21 articles met the research objectives based on the established inclusion and exclusion criteria. The study found a growing trend in the use of interactive learning media in elementary schools, with China emerging as the country with the highest number of relevant publications. Most of the research focuses on STEM subjects and utilizes online learning platforms. The study also revealed that the majority of interactive learning media are multimedia-based, making them engaging and enhancing student motivation. These findings serve as recommendations for future researchers to develop multimedia-based interactive learning media that accommodate various student learning styles. This report provides a scientific foundation for policymakers to establish best practices for the use of technology in education.